Implementation of Variable Speed Drive as Starting Control of Three Phase Induction Motor - Prasetia, Abdul Muis; Sartika, LInda; Sanjaya, Dhani; Samanta, Rizal (Jurnal Edukasi Elektro, 2024)
The three-phase induction motor is a prevalent electrical machine utilized across various industrial applications. Notably, the surge current of the induction motor can range from five to seven times the nominal current. This research aims to address this issue by identifying an appropriate three-phase induction motor. One effective method for operating three-phase induction motors is through the implementation of a Variable Speed Drive (VSD). This study develops an induction motor starting system utilizing VSD technology to mitigate the surge current associated with three-phase induction motors. Frequency and duty cycle variations were tested to evaluate their impact. Adjusting the frequency from 25 to 75 Hz at a VSD output voltage of 220 V resulted in a current reduction of 0.74 A. Conversely, modifying the duty cycle from 10% to 100% at a frequency of 50 Hz led to an increase in current of 1.136 A.